2008
DOI: 10.1007/s00383-008-2123-y
|View full text |Cite
|
Sign up to set email alerts
|

Tissue damage in rat ovaries subjected to torsion and detorsion: effects of l-carnitine and N-acetyl cysteine

Abstract: We aimed to evaluate histopathological changes, to detect HIF-1alpha staining intensities and to determine MDA levels in rat ovaries, which were subjected to torsion and detorsion and treated with L -carnitine or N-acetyl cysteine (NAC). Forty-eight prepubertal female Sprague-Dawley rats were divided into five groups (n = 8): 1, control; 2, ischemia; 3, reperfusion; 4, L -carnitine; and 5, NAC groups. In groups 3, 4 and 5, an ischemic period of 3 h was followed by reperfusion for 24 h. In groups 4 and 5, ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…Lipid peroxidation is measured by tissue MDA assay as an indirect index of reactive oxygen metabolites and a biochemical marker of tissue I/R injury (Erkasap et al, 2004). In this study, the MDA level increased significantly after I/R induction, as in previous studies (Aragno et al, 2003;Sahin et al, 2008;Sehirli et al, 2003;Usta et al, 2008). Our results showed that beta-carotene administration significantly reduced MDA production.…”
Section: Discussionsupporting
confidence: 78%
“…Lipid peroxidation is measured by tissue MDA assay as an indirect index of reactive oxygen metabolites and a biochemical marker of tissue I/R injury (Erkasap et al, 2004). In this study, the MDA level increased significantly after I/R induction, as in previous studies (Aragno et al, 2003;Sahin et al, 2008;Sehirli et al, 2003;Usta et al, 2008). Our results showed that beta-carotene administration significantly reduced MDA production.…”
Section: Discussionsupporting
confidence: 78%
“…N-acetylcysteine (NAC) is a precursor of intracellular cysteine and reduced glutathione and a proven potent antioxidant in various tissue types (Danilovic et al, 2011;Inci et al, 2007;Usta et al, 2008). Following intraperitoneal injection of 150 mg/kg NAC daily for 7 days, folliculogenesis in WT mice did not differ detectably from that of mice injected with PBS only (WT+ PBS; data not shown).…”
Section: N-acetylcysteine Treatment Rescues the Kat8 Null Phenotypementioning
confidence: 98%
“…This causes endothelial injury, increases microvascular permeability and tissue swelling, as well as starting the inflammatory responses through activation of adhesion molecules and enhanced cytokine production (Damous et al, 2009;Khan et al, 2004). The production of ROS is also directly involved in the oxidative damage of cellular macromolecules, such as nucleic acids, proteins and lipids in ischaemic tissues (Usta et al, 2008). All of these events can lead to a massive follicular loss in the transplanted ovarian tissue (Damous et al, 2009;Gao et al, 2013;Hirayama et al, 2011;Kim, 2010;Skaznik-Wikiel et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…N-acetylcysteine (NAC) has been extensively studied as a potent antioxidant in several studies (Danilovic et al, 2011;Inci et al, 2007;Usta et al, 2008). It is an aminothiol, a precursor of intracellular cysteine and reduced glutathione (Inci et al, 2007;Sun, 2010), which easily penetrates the cell membranes (Usta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%